Kedokteran : PreTest uji diri da pembahasan Roger D. Smalligan... [et al] ; penerjemah, Melfiawati ; penyunting, Tim Indeks - Roger D. Smalligan; Melfiawati; Tim indeks (Indeks, 2013)
x, 538 hlm. ilus. 21 cm. (3 eks.)